Canine cutaneous melanocytic tumors: main histopathological parameters and the use of a magenta chromogen in immunohistochemical diagnosis - Contel, Isabeli Joaquim [UNESP]; Ferrari, Heitor Flavio; Laufer-Amorim, Renee [UNESP]; Xavier Júnior, José Cândido Caldeira [UNESP] (Springer Nature, 2025)
Histopathological analysis remains the gold standard for diagnosing canine melanocytic tumors, and immunohistochemistry as an auxiliary tool. Given the challenge for immunohistochemical interpretation posed by melanin, a common pigment in the cytoplasm of canine neoplastic melanocytes, particularly when using 3,3’-diaminobenzidine (DAB) chromogen, this study aimed to evaluate the applicability of a magenta-colored chromogen for revealing the immunoreactivity of the well-established antibody Melan-A in 40 canine pigmented cutaneous melanocytic tumors and to analyze the association between several histopathological parameters and the diagnosis. Among the samples, 23 were classified as melanocytomas and 17 as melanomas. Significant associations were found between histopathological diagnosis and parameters such as ulceration, nuclear atypia, pigmentation, modified Clark level, symmetry, tumor margins, predominant cellular morphology, intratumoral necrosis, and lymphoplasmacytic inflammatory infiltrate (p < 0.05). A significant difference in the mean mitotic count was also observed between melanomas and melanocytomas (p < 0.05). All samples were positive for Melan-A. Most melanocytic tumors were heavily pigmented, and from these tumors, the majority exhibited strong cytoplasmic Melan-A immunostaining. The magenta chromogen provided excellent contrast with melanin and was visible in tumors regardless of pigmentation level. The findings of this study underscore the importance of analyzing specific histopathological parameters, which might help to differentiate benign from malignant lesions. Also, our results indicate that the magenta chromogen is both applicable and effective in the analysis of pigmented canine cutaneous melanocytic tumors, mitigating the interference caused by melanin and serving as a viable alternative to DAB in conventional immunohistochemistry. Additionally, these findings open perspectives for future studies applying the magenta chromogen to other melanocytic lineage markers.